A Solvent‐free Strategy to Prepare Amorphous Salts of Folic Acid with Enhanced Solubility and Cell Permeability. Issue 6 (1st February 2022) - Martins, Inês C. B.; Forte, Andreia; Diogo, Hermínio P.; Raposo, Luís R.; Baptista, Pedro V.; Fernandes, Alexandra R.; Branco, Luís C.; Duarte, M. Teresa
Abstract: Eight new amorphous organic salts of folic acid (FA) were prepared by mechanochemistry. FA can prevent cardiovascular and neurological diseases. Mechanochemistry overcomes serious FA solubility issues avoiding the use of toxic solvents. Due to low FA solubility, therapeutic effects in supplements and drugs are not achieved. Current strategies to improve FA solubility include its derivatization by using complex synthetic procedures. Herein, a simple and green procedure, avoiding structural modifications, was designed using mechanochemistry. Biocompatible amine‐derivative coformers were strategically combined with FA to obtain salts with good physicochemical properties. New 1 : 1 and 1 : 2 amorphous FA salts offer 10 to 10, 000 times better aqueous solubility and 10 to 100 times better octanol‐water partition coefficient values (Koctanol/water ) than FA alone. Koctanol/water is considered as a surrogate of cell permeability. No toxic effects in normal human primary dermal fibroblasts were detected for the prepared FA salts. Our findings suggest that 1 : 2 FA salts of choline hydroxide and derivatives could be good candidates for future pharmaceutical/nutraceutical applications. Abstract : Eight new amorphous salts of folic acid (FA) were prepared by mechanochemistry, a green method. The solubility and octanol‐water partition coefficient (cell permeability) of FA were remarkably improved with no toxic effect, making them good candidates for pharmaceutical/nutraceutical applications.